Systematic Review: Impact of Air Pollution on DNA Methylation - Akbar, Muhammad Ihzario Ibrahim; Tualeka, Abdul Rohim; Zurimi, Suardi; Jalaludin, Juliana (Media Gizi Kesmas, 2025)
Background: Quality of life is an important. It is influenced by exposure to chemicals in the body, such as air pollution, which can damage supporting life in the future. Objective: The aim of writing this systematic review is to specify the impact of air pollution on DNA methylation. Methods: The method in this study uses the Preferred Reporting Items for Systematic Review and Meta-analyses, this methode is carried out by searching for data in the form of articles or journals, which is carried out using the keywords "Air pollution" and "DNA methylation". Overall data from articles or jurnals based on searches using the keywords "Air pollution" and "DNA Methylation" (n=25), data from articles or journals focused on this research and articles or journals that can be accessed for free with the year publication year in the last 10 years (n=20), after which they are adjusted to the inclusion criteria of this study (n=15). Result: In this study, the results of the systematic review were obtained that this long-term impact will affect a person's quality of life, apart from that, it can also cause serious complications such as repeated respiratory infections, which can lead to decreased lung function and a higher risk of death. Conclusion: DNA is a logical tool for understanding the impact of air pollution on genome function and downstream activities that benefit health.